Electrospun Fibers: Versatile Approaches for Controlled Release Applications - Sepideh Karimi Afshar; Mohammadmohsen Abdorashidi; Farid Abedin Dorkoosh; Hamid Akbari Javar (International Journal of Polymer Science)
Electrospinning has been one of the most attractive methods of fiber fabrication in the last century. A lot of studies have been conducted, especially in tissue engineering and drug delivery using electrospun fibers. Loading many different drugs and bioactive agents on or within these fibers potentiates the efficacy of such systems; however, there are still no commercial products with this technology available in the market. Various methods have been developed to improve the mechanical and physicochemical behavior of structures toward more controllable delivery systems in terms of time, place, or quantity of release. In this study, most frequent methods used for the fabrication of controlled release electrospun fibers have been reviewed. Although there are a lot of achievements in the fabrication of controlled release fibers, there are still many challenges to be solved to reach a qualified, reproducible system applicable in the pharmaceutical industry.